Exploring the intersection of religion and literature: Insights from “Komunitas Pondok Pena Banyumas” as Indonesia pesantren literary communities - Febriani, Meina; Nuryatin, Agus; Supriyanto, R.M. Teguh; Mardikantoro, Hari Bakti (Research Journal in Advanced Humanities, 2024)
Religion and literature are two different things. On the one hand, literature is known as a vehicle for freedom of expression, but on the other hand, there are religious values. The case study “Komunitas Pondok Pena” An Najah Islamic Boarding School, Banyumas, Indonesia, has carried out literary activities. This article reveals two things: (1) how the community of Pondok Pena Banyumas incorporates religious values in literary works and (2) how Islamic boarding school cultural values influence the literary creative process. The research method used is a qualitative approach with a case study design. Data was obtained through non-participatory observation techniques, and intensive interviews. The research results show that first, religious values are a source of inspiration and worldview for the students which are reflected in the literary works produced; Second, Islamic boarding school cultural values are implemented in the literary creative process which is reflected in the world of Islamic boarding school life.